2022
DOI: 10.1039/d1tc05944k
|View full text |Cite
|
Sign up to set email alerts
|

Antiferroelectric-to-ferroelectric phase transition in hexagonal rare-earth iron oxides

Abstract: Ferroic oxides often exhibit exotic behavior, accompanied by phase transitions. Hexagonal rare-earth iron oxides (h-RFeO3), a promising multiferroic system, were reported to exhibit ferroelectricity (FE) when the lattice parameter ratio...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…The antiferroelectric-to-ferroelectric transition by increasing E max is a consequence of an increase in the migration length of the domain wall. 26 Similar transitions were observed in the h-RMnO 3 films, with R having a larger Z (R = Tb, Dy). 20,21 The P r and coercive electric field (E c ) values of the film were 2.1 μC/cm 2 and 0.15 MV/cm, respectively.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…The antiferroelectric-to-ferroelectric transition by increasing E max is a consequence of an increase in the migration length of the domain wall. 26 Similar transitions were observed in the h-RMnO 3 films, with R having a larger Z (R = Tb, Dy). 20,21 The P r and coercive electric field (E c ) values of the film were 2.1 μC/cm 2 and 0.15 MV/cm, respectively.…”
Section: Resultssupporting
confidence: 56%
“…Conversely, at E max = 1.4 MV/cm (Figure b), the P – E curve of the h-ErFeO 3 film showed a clear single ferroelectric hysteresis loop, indicating the ferroelectric behavior of the film at high E max regions. The antiferroelectric-to-ferroelectric transition by increasing E max is a consequence of an increase in the migration length of the domain wall . Similar transitions were observed in the h-RMnO 3 films, with R having a larger Z (R = Tb, Dy). , The P r and coercive electric field ( E c ) values of the film were 2.1 μC/cm 2 and 0.15 MV/cm, respectively.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…h-R FeO 3 nanoparticles can be synthesized by wet-chemical or supercooling methods, although it is difficult to characterize the ferroic properties owing to the existence of impurity phases and their small size. A more effective method is the epitaxial thin-film growth on single-crystal substrates, such as YSZ(111) and Al 2 O 3 (0001) substrates. A series of h-R FeO 3 ( R = Sc, Y, and Gd–Lu) epitaxial films have been fabricated without impurity phases. It is suggested that the metastable h-R FeO 3 phase is stabilized owing to the lattice match between the film and single-crystal substrate. Compared to single-crystal substrates, glass substrates are more cost-effective, which is important for future applications.…”
Section: Introductionmentioning
confidence: 99%